2015
DOI: 10.1016/j.ajo.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcomes of Aflibercept in Recurrent or Persistent Neovascular Age-Related Macular Degeneration

Abstract: Purpose To evaluate 6-month and 1-year outcomes of every 8 weeks (Q8W) aflibercept in patients with resistant neovascular age-related macular degeneration (AMD). Design Retrospective, interventional, consecutive case series. Methods Retrospective review of patients with resistance (multiple recurrences or persistent exudation) to every 4 weeks (Q4W) ranibizumab or bevacizumab that were switched to Q8W aflibercept. Results Sixty-three eyes of 58 patients had a median of 13 (interquartile range (IQR), 7-22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
57
1
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 18 publications
5
57
1
7
Order By: Relevance
“…It is possible that in unresponsive patients, switching to a higher frequency of aflibercept injections would result in a more favorable outcome. (Arcinue et al 2015) Whereas, all our patients demonstrated a reduction in CRT following conversion, the visual function did not change accordingly, suggesting that in patients with continued visual deterioration despite anatomical stability, changing agents may be advised to achieve maximal therapeutic effect. …”
mentioning
confidence: 57%
“…It is possible that in unresponsive patients, switching to a higher frequency of aflibercept injections would result in a more favorable outcome. (Arcinue et al 2015) Whereas, all our patients demonstrated a reduction in CRT following conversion, the visual function did not change accordingly, suggesting that in patients with continued visual deterioration despite anatomical stability, changing agents may be advised to achieve maximal therapeutic effect. …”
mentioning
confidence: 57%
“…In contrast, in our study, the dry macula and unchanged, increased, and decreased visual acuity rates at 3 months after the aflibercept injections were 38.1%, 42.9%, 42.8%, and 14.3%, respectively, in the tachyphylaxis group, and 39.1%, 43.5%, 34.7%, and 21.7%, respectively, in the complete resistance group. The high rate of dry macula in the study by Arcinue et al can be largely attributed to the inclusion of both recurrent and persistent cases in the working group (15) . Studies have shown that intravitreal aflibercept injections are also effective against other anti-VEGF resistant PEDs (3,27) .…”
mentioning
confidence: 89%
“…A retrospective study by Arcinue et al, one of the most recent studies on this subject, observed an average visual acuity increase of 0.05 logMAR together with a dry macula in 60.3% of the eyes at the end of 6 months (15) . Additionally, visual acuity remained unchanged in 38.1% of the eyes, an increase of ≥1 line was observed in 36.5% of the eyes, and a decrease of ≥1 line was observed in 23.8% of the eyes.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…37,38 This is in contrast to AMD where the effect of switching between anti-VEGFs in resistant cases has been studied extensively. [39][40][41][42][43][44][45] Switching to both aflibercept and ranibizumab has been attempted, with resistant cases usually showing variable degrees of improvement, making this strategy a reasonable option in cases of AMD.…”
Section: Aflibercept In Non-naive Eyes (Secondary Therapy)mentioning
confidence: 99%